AKSELERASI PENYELESAIAN PROYEK DENGAN ANALISA PERTUKARAN WAKTU DAN BIAYA ( TIME COST TRADE OFF ) - Sudarsana, Dewa Ketut (Jurnal Ilmiah Teknik Sipil; Vol. 9, No. 1 Januari 2005, 2012)
Three main objective in the constructing construction project there are cost, time and quality. Cost and time have great relationship and depending once than the other. Some time in the field we founded nonconform between the duration of completion in the contract with the realization. On the case studi of Pembangunan Stadion Olah Raga Buruan in Kecamatan Blahbatuh, Gianyar, the owner need that project be completed earlier than the agreement completion. The influence of acceleration completion project with the project cost need to study. In this case the CPM (Critical Path Method) be used with compressed the duration of activities on the critical path and do time cost trade off analysis. The project cost means is the total cost project. The total project cost are direct cost (material, workers and equipment) and indirect cost (the other direct cost). The outcome of analysis be founded that accelerate (crash) maximum 65 days done, so the earliest completion by 265 days without total project cost added. The project completion optimum be founded too, with project duration 316 days and project total cost minimum amount Rp. 13.358.425.131,28, that’s below 0.55 % than project cost in contract. This phenomenon show that accelerate the duration completion project not always be increasing the total project cost, because the duration of completion project in the contract probably does not the optimum duration of completion.
Keywords: accelerate duration, project cost, time cost trade off